2012
DOI: 10.1016/j.biomaterials.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of interfacial radical polymerization initiated by a glucose-oxidase mediated redox system

Abstract: The reaction and coating kinetics for the glucose oxidase initiated interfacial polymerization are elaborated. The interfacial film grows rapidly and linearly with time, producing time-dependent controllable conformal coating thicknesses of up to a millimeter in less than 4 minutes. Bulk polymerization was only observed when the immersing media was stirred to induce higher mass transport rates. The dramatically different film thicknesses observed between different concentrations of glucose in the hydrogel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…The thiol-ene interfacial photopolymerization developed here is similar to the GOx-mediated coating system developed by Johnson and Bowman et al 2022 and the interfacial PEG-diacrylate (PEGDA) photopolymerization system pioneered by Hubbell et al 3, 9, 2830 The major differences between our system and the previous ones are two-fold: (1) our coating chemistry is a step-growth gelation mechanism, and (2) the macromer solution used in our thiol-ene interfacial coating procedures contained only macromers (i.e., PEG4NB and DTT) without additional co-initiator or co-monomer. Further, our controlled experiments demonstrated that this interfacial cross-linking was not due to initiator-free thiol-ene photopolymerization as gelation was not observed after prolonged light exposure (> 1 hour) without the presence of eosin-Y (data not shown).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The thiol-ene interfacial photopolymerization developed here is similar to the GOx-mediated coating system developed by Johnson and Bowman et al 2022 and the interfacial PEG-diacrylate (PEGDA) photopolymerization system pioneered by Hubbell et al 3, 9, 2830 The major differences between our system and the previous ones are two-fold: (1) our coating chemistry is a step-growth gelation mechanism, and (2) the macromer solution used in our thiol-ene interfacial coating procedures contained only macromers (i.e., PEG4NB and DTT) without additional co-initiator or co-monomer. Further, our controlled experiments demonstrated that this interfacial cross-linking was not due to initiator-free thiol-ene photopolymerization as gelation was not observed after prolonged light exposure (> 1 hour) without the presence of eosin-Y (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…The unique visible light-mediated interfacial thiol-ene gel coating system is comparable to the glucose oxidase (GOx) mediated gel coating system reported by Bowman and colleagues. 2022 The GOx-mediated gel coating system, however, uses multiple initiator components (i.e., GOx, glucose, and ferrous ion) to initiate polymerization reactions. Because the process produces highly cytotoxic hydrogen peroxide (H 2 O 2 ), a second enzyme, catalase, has to be included in the macromer solution to prevent cellular damage.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier investigation,5 we reported that glucose oxidase is trapped by the propagating polymerization front; however, the concentration of the active enzyme is significantly lower than the concentration of the bulk enzyme. This outcome arises as a result of inefficiency in encapsulation as well as inactivation of the enzyme by hydrogen peroxide where the inactivation by hydrogen peroxide has been extensively investigated in the literature 21–24.…”
Section: Model Developmentmentioning
confidence: 77%
“…However, one representative value for the enzyme fraction trapped is used for all experimental conditions. To obtain the values for these unknown constants, the model prediction for the time‐dependent thickness was fit to the experimental data reported earlier for two cases 5. In the first case, the enzymatic precursor for film formation is the glucose oxidase (GOx) in the bulk media (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation